Triangle [compact disc, unabridged] - Steel, Danielle (Recorded Books, 2024)
Parisian art gallery owner Amanda Delanoe finds herself entangled in a dangerous mystery as she approaches her fortieth birthday. Caught between two men - the charming publisher Olivier and her old flame Tom - Amanda's life takes a thrilling turn when she begins receiving threatening messages. With the help of her friend Pascal, Amanda must navigate the complexities of love and danger in the City of Light.